The potential of salivary biomarkers of nutritional status and dietary intake: A Systematic Review. (December 2021) - Logan, D.; Wallace, S.M.; Woodside, J.V.; McKenna, G.
Abstract: Objectives: To explore whether nutritional salivary biomarkers could be used to aid nutritional status assessment and/or support traditional dietary assessment methods for patients. Data and Sources: Searches were performed using four electronic databases; MEDLINE, EMBASE, Scopus and Web of Science. Trial registers (i.e. Cochrane), grey literature and reference lists were searched. Study Selection: Studies which measured nutritional salivary biomarkers related to nutritional status and/or dietary intake outcome were included. No restrictions on participants' age, study design, publication date, setting or health status. Animal studies, non-English language studies, commentaries, and conference abstracts were excluded. Results: Study titles and abstracts were screened ( n  = 7982), full-texts assessed ( n  = 176) and 85 studies were included in a narrative synthesis. The most promising salivary biomarkers for nutritional status included: glucose, where saliva and serum levels were positively correlated in those with type 2 diabetes (T2D), higher salivary calcium levels in post-menopausal women in general and specifically those with lower bone mineral density (BMD), and salivary vitamin D to assess vitamin D status in healthy volunteers. Higher salivary total antioxidant capacity (TAC), nitrate/nitrite and fluoride were observed with increased antioxidant, nitrate/nitrite and fluoride dietary intake, respectively. A meta-analysis found significantly higher mean salivary glucose ( n  = 12) in T2D compared with healthy controls, but there was substantial heterogeneity (I 2 =94%) and evidence of publication bias. Conclusions: The most promising salivary biomarkers identified in this systematic review were, glucose, vitamin D, calcium, TAC, nitrate/nitrite and fluoride. However, this was based on a small number of studies of varying quality, with many lacking a salivary assay performance assessment. Clinical Significance: At present, nutritional salivary biomarkers cannot be used alone to assess nutritional status or dietary intake. Further research into the most promising nutritional salivary biomarkers is required.